Uptake and processing of glycoproteins by rat hepatic mannose receptor - Taylor,ME; Leaning,MS; Summerfield,JA (American Journal of Physiology Endocrinology and Metabolism, 1987)
A linear compartmental model has been developed for the in vivo metabolism of glycoproteins. The model is applied to the interpretation of dynamic data from the rat on agalactoorosomucoid (AGOR), an N-acetylglucosamine (GlcNAc)-terminated glycoprotein, and three neoglycoproteins terminating in mannose [mannose36-bovine serum albumin (Man-BSA)] or glucose [maltose29-BSA (Mal29-BSA) and maltose8-BSA (Mal8-BSA)]. All of these proteins are taken up by the Man/GlcNAc receptor on hepatic sinusoidal cells. The rate of uptake was found to be determined by sugar type (Man-BSA, 0.78 min-1 > Mal29-BSA, 0.13 min-1), sugar density (Mal29-BSA > Mal8-BSA), and the geometry of the sugar display (AGOR, 0.51 min-1 > Mal29-BSA). Intracellular transport from the cell membrane to the lysosomes was slower for Man-BSA (~3 min) than for the other ligands (~0 min), suggesting that receptor-ligand uncoupling was slower for Man-BSA for which the receptor had the highest affinity or that extralysosomal catabolism of the other ligands occurred. Catabolism was also determined by the carbohydrate moiety of the ligand; it was greater for Mal29-BSA and Mal8-BSA (≥0.8 min-1) than for Man-BSA (0.27 min-1), and AGOR, with a complex oligosaccharide, was most resistant to degradation (0.14 min-1). An understanding of these structural features of glycoproteins that influence hepatic uptake, transport, and catabolism will be of value in drug targeting and for enzyme replacement in lysosomal storage disorders. Special emphasis is placed on model identifiability before experimentation as an aid in experiment des